Rancang Bangun Sistem Informasi Pencarian Kost Menggunakan Metode RAD (Studi Kasus: Plaju Palembang) - Nabilah Afifa Sari; Syarifah Aini; Muhammad Ihsan (Journal of Innovative and Creativity, 2025)
The purpose of this study was to design and develop an information system for boarding house (kost) search in the Plaju area of Palembang using the Rapid Application Development (RAD) method. The system aims to facilitate students and newcomers in finding available boarding houses efficiently without the need to visit each location manually. This study was motivated by the challenges faced by students from outside Palembang who struggle to obtain accurate and up-to-date information about available kosts near their campuses. The research applied the RAD methodology, which emphasizes fast and iterative development through three main stages: requirement planning, design workshop, and implementation. Data were collected through observation and literature studies to analyze user needs and system requirements. The system was developed using PHP, HTML, JavaScript, and MySQL, with Unified Modeling Language (UML) tools such as use case diagrams, activity diagrams, and class diagrams used to model the system. Black-box testing was performed to evaluate system functionality. The resulting web-based application allows users to view detailed kost information, including prices, facilities, and locations, and to contact the owner directly via WhatsApp. The system also includes features for admin and owner management of kost data. Testing results show that all system functions performed as expected, and the RAD approach enabled faster development and higher user satisfaction. The RAD-based kost information system successfully streamlines the search and management of kost data in Plaju. It improves accessibility and efficiency for users and owners. Future improvements could include Android integration, enhanced user interface design, and online hosting for broader accessibility.